THE OUTCOMES OF BUTTERFLY STROKE IN SWIMMING - Ishak, Muchamad (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The purpose of this study was to look for the effectiveness of teaching styles on learning outcomes seen flexibility inswimming ability. The method used is experiment with a 2x3 factorial design treatment. Research conducted at STKIP Pasundan Cimahi with a sample of students Prodi PJKR. The results of the study concluded that: (1) There are differences in butterfly stroke in swimming between inclusion and reciprocal teaching styles altogether (2) There are differences in butterfly stroke in swimming between inclusion and command teaching styles altogether, (3) There are differences in butterfly stroke in swimming between reciprocal and command teaching styles altogether, (4) There is an interaction between teaching styles and flexibility toward butterfly stroke in swimming altogether, (5) There are differences in butterfly stroke in swimming between inclusion and reciprocal teaching styles toward high flexibility (6)There are differences in butterfly stoke in swimming between inclusion and commando teaching styles toward high flexibility, (7) There are differences in butterfly stroke in swimming between reciprocal and commando teaching style toward high flexibility, (8) There are differences in butterfly stroke in swimming between inclusion and reciprocal teaching styles toward low flexibility (9)There are differences in butterfly stoke in swimming between inclusion and commando teaching styles toward low flexibility, and (10) There are differences in butterfly stroke in swimming between reciprocal and commando teaching style toward low flexibility.